Strategic Development of Human Resource Management as a Key Pillar of Industry in the Digital Era - Kusumaningrum, Yetty Yuliany; Arifah, Reni Nur (Yayasan Meira Visi Persada, 2026)
Technological developments, digitalization of work processes, and changing work patterns require industries to have adaptive, innovative, and highly competitive human resources. The era of globalization has created highly dynamic industrial competition, and human resource (HRM) management plays a strategic role in enhancing industrial competitiveness. This study analyzes effective human resource management (HRM) development strategies to address the challenges of globalization. The research method used was descriptive qualitative, reviewing literature from various relevant sources. The results indicate that human resource development must be carried out comprehensively through competency training, leadership development, and the use of digital technologies, such as HRIS systems. A multinational work culture and reskilling and upskilling strategies are key to maintaining industrial productivity and innovation. The implementation of these strategies is expected to become a key pillar of the digital industry and increase production process efficiency, creating a competent, loyal, and productive workforce in the global era